Efficiency Analysis of Capture Fisheries in the Northern and Southern Coastal Regions of Central Java, Indonesia - Hapsari Ayu Kusumawardhani; Arisanti Ayu Wardhani (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
This study examines the fishery efficiency in the northern and southern coastal regions of Central Java by applying the Data Envelopment Analysis (DEA) approach. The efficiency measurement is based on three input variables (number of fishermen, boats, and fishing gear) and two output variables (total production value and quantity of fish produced). The analysis reveals that Tegal City is the most efficient region in Central Java's fisheries sector, followed by Rembang, Pati, and Batang. These regions demonstrate relatively optimal utilization of available fishing resources to generate high output. Tegal's efficiency can be attributed to its integrated fishing infrastructure, better market access, and effective fleet and labor management. In contrast, other regions showed lower efficiency due to underutilization of resources or operational constraints. The findings suggest the need for targeted policies to enhance technical efficiency in lagging areas, such as capacity-building programs, modernization of fishing gear, and improved value chain integration to support a more balanced and sustainable fisheries development across Central Java.